Patagonian shellfish and hidden threats: unveiling the viral landscape and the first quantitative microbial risk assessment of Argentine bivalve mollusks - Frydman, Camila Ayelén; Parreño, Gladys Viviana; Cap, Mariana; Galeano, Fabiana Solange; Signorini Porchiett, Marcelo Lisandro; Mozgovoj, Marina Valeria (Elsevier, 2026)
Foodborne viral infections are a global public health concern, yet quantitative risk assessments (QMRA) for enteric viruses in bivalve mollusks are scarce, especially in South America. We conducted Argentina's first QMRA for five human enteric viruses- norovirus (NoV), rotavirus A (RVA), hepatitis A (HAV), hepatitis E (HEV), and adenovirus (AdV) in bivalve mollusks. From August 2018–March 2023, 390 specimens from Golfo Nuevo, Chubut, were pooled (n = 113) and analyzed by real time PCR. A national survey revealed 3.6 % of servings were raw or minimally cooked. AdV showed the highest prevalence and viral load, followed by NoV GII and RVA; HAV and HEV had lower loads, and NoV GI was undetected. Per-serving infection risks peaked for AdV and NoV GII from raw oyster and mussel consumption. Individual annual infection probabilities were 2.44 × 10−1 for AdV, 1.33 × 10−1 for NoV GII, and 6.60 × 10−2 for HAV. RVA and HEV posed lower risks. Sensitivity analysis identified AdV and HAV prevalence, and mussel and clam consumption, as key drivers of the shellfish-associated infection risk. Our findings pinpoint raw and undercooked oysters and mussels as significant sources of risk. This QMRA provides crucial, country-specific evidence to support optimizing disinfection processes and enhancing monitoring of critical environmental contamination sources along the seafood production and distribution chain.